APPLICATION OF E-GOVERNANCE IN EDUCATION SECTOR TO ENHANCE THE QUALITY OF EDUCATION AND HUMAN RESOURCE DEVELOPMENT IN BANGLADESH - Md. Assraf Seddiky; Esmat Ara (European Scientific Journal, ESJ, 2015)
Education is one of the most important factors in achieving the development goals of any country. In Bangladesh, Education has seen massive growth in recent years due to the application of e- governance in this sector. Information and Communication Technology initiatives help to provide of world-class education. The application of e-governance in education sector has led to a new broader of innovations. The purpose of this study is to examine how and to what extent e-governance enhances the quality of education as well as human resource development. This study is conducted following both qualitative and quantitative research approach based on primary and secondary data. To validate research data sample survey method is used in this study. Semi-structured questionnaire has been applied to collect data from the respondents through face to face interview. 120 Sample populations have been selected from the teachers, students and officials of Shahjalal University of Science and Technology, and Government College, Sylhet, Bangladesh, taking sixty from each institution through systematic sampling method. Secondary data collected from different published materials like books, articles, reports by academics and regular internet surfing has been maintained to serve the purpose of the study. Study findings reveal that in spite of having some limitations, information and communication technology contributing a lot to improve the quality of education and to develop human skills making them fit for the competitive global market. Researcher believes that, the study findings will hopefully be a guideline for future researchers and academics for further study on the very issue from different angle calling attention to policy makers in this regard.